Rozwój filmowych adaptacji komiksów – „kino superbohaterskie” jako gatunek - Czyżak, Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
This article is an attempt to consider superhero movies as a developing genre of popular cinema. The theory is based on Rick Altman’s “Semantic/Syntactic/Pragmatic” approach to genre. It tries to capture features of superhero blockbusters and their main themes – the most distinctive trait of this genre, according to the author of the text, is supposed to be the relationship between an individual, their “power” and society. The text is both an extension of and a counter-proposal to conclusions made by Tomasz Żaglewski in Kinowe uniwersum superbohaterów.